Prostate cancer: The main risk and protective factors - Epigenetic modifications - KARSLI, SEHER (MASSON EDITEUR, 2015)
With 13 million new cases worldwide every year, prostate cancer is as a very real public health concern. Prostate cancer is common in over-50s men and the sixth-leading cause of cancer-related death in men worldwide. Like all cancers, prostate cancer is multifactorial - there are non-modifiable risk factors like heredity, ethnicity and geographic location, but also modifiable risk factors such as diet. Diet-cancer linkages have risen to prominence in the last few years, with accruing epidemiological data pointing to between-population incidence differentials in numerous cancers. Indeed, there are correlations between fat-rich diet and risk of hormone-dependent cancers like prostate cancer and breast cancer. Diet is a risk factor for prostate cancer, but certain micronutrients in specific diets are considered protective factors against prostate cancer. Examples include tomato lycopene, green tea epigallocatechin gallate, and soy phytoestrogens. These micronutrients are thought to exert cancer-protective effects via anti-oxidant pathways and inhibition of cell proliferation. Here, we focus in on the effects of phytoestrogens, and chiefly genistein and daidzein, which are the best-researched to date. Soy phytoestrogens are nonsteroid molecules whose structural similarity lends them the ability to mimic the effects of 17 beta-estradiol. On top of anti-oxidant effects, there is evidence that soy phytoestrogens can modulate the epigenetic modifications found in prostate cancer. We also studied the impact of phytoestrogens on epigenetic modifications in prostate cancer, with special focus on DNA methylation, miRNA-mediated regulation and histone modifications. (C) 2014 Elsevier Masson SAS. All rights reserved.
Keywords: Prostate cancer; Diet; Phytoestrogens; Risk factors; Epigenetics; PREVENTION TRIAL SELECT; GREEN TEA POLYPHENOLS; DNA METHYLATION; CELL-LINES; BREAST-CANCER; EARLY-ONSET; VITAMIN-E; PROMOTER HYPOMETHYLATION; TRANSCRIPTIONAL ACTIVITY; MICRORNA EXPRESSION